Managing risk and security: How humanitarian organisations adapt in conflict zones - Messerschmidt,Marie-Luisa; Guth,Emelie (2025)
Humanitarian aid workers (HAWs) face increasing risks in conflict zones, with 2024 marking the deadliest year on record. International humanitarian organisations (IHOs) must address this trend to continue delivering aid and protecting HAWs. This study investigates how IHOs adapt to the evolving risks in these contexts and explores challenges that adaptation measures may entail. A qualitative research design with a constructivist grounded theory approach was employed, using semi-structured interviews with 12 key informants from three IHOs, supported by secondary sources. Two themes were identified: (1) understanding contextual factors and (2) politicisation of humanitarian aid (HA). Risks were described as context-dependent, with threats increasingly coming from governments and a reduced respect for International Humanitarian Law (IHL). To remain resilient, IHOs rely on soft and context-sensitive approaches. Adaptation measures include internal processes such as risk assessments grounded in local understanding, context-appropriate staff employment, and ensuring transparency and informed consent. These support external approaches, including acceptance strategies through negotiation, community engagement, provision of relevant aid, and advocacy. Challenges involve the meaningful incorporation of local perspectives, trade-offs in staff selection, and reduced adaptive flexibility due to the professionalisation of security risk management (SRM). Violations of IHL and a lack of accountability hinder these efforts. This study shows that adaptation is influenced by both internal strategies and external actors, embedded in contextual dependencies, social dynamics and power structures. Tensions between SRM practices and actual protection, as well as the shifting nature of threats should be explored further.
Keywords: Security risk management; humanitarian aid; humanitarian aid worker; conflict zones; adaptation; politicisation; acceptance.